2018
DOI: 10.1007/s00062-018-0662-8
|View full text |Cite
|
Sign up to set email alerts
|

Reversible Dilation of Cerebral Macrovascular Changes in MELAS Episodes

Abstract: Reversible dilation of cerebral macrovascular changes could be a new feature of MELAS and a presumed reason for fluctuant CBF. It would shed new light on the mitochondrial angiopathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 31 publications
1
14
0
Order By: Relevance
“…MRA has not been routinely performed in MELAS in the past, because major cerebral vessels were considered to be the target of mitochondrial metabolism defects in these patients. However, more and more studies have found major cerebral vessels dilation ( 39 , 44 , 45 ) or stenosis ( 46 , 47 ) on MRA in MELAS in the acute and chronic stages of the disease. Gramegna et al ( 48 ) found that the proportion of cerebral major vessels dilation and stenosis was 40 and 19%, respectively, on MRA, and the middle cerebral artery was the most commonly involved.…”
Section: Funtional Mri Findingsmentioning
confidence: 99%
“…MRA has not been routinely performed in MELAS in the past, because major cerebral vessels were considered to be the target of mitochondrial metabolism defects in these patients. However, more and more studies have found major cerebral vessels dilation ( 39 , 44 , 45 ) or stenosis ( 46 , 47 ) on MRA in MELAS in the acute and chronic stages of the disease. Gramegna et al ( 48 ) found that the proportion of cerebral major vessels dilation and stenosis was 40 and 19%, respectively, on MRA, and the middle cerebral artery was the most commonly involved.…”
Section: Funtional Mri Findingsmentioning
confidence: 99%
“…In patient 8, who had bilateral SLLs in the parietal lobes, matching dilation of the MCA and dilatation of the right ACA were found [1]. We do not agree that the right ACA matches with a right parietal SLL.…”
mentioning
confidence: 58%
“…In a recent article by Li et al [1], a study of cerebral perfusion in 20 patients with mitochondrial encephalopathy, lactic acidosis, and stroke-like episodes (MELAS) by MRI/MRA was presented. We have the following comments/concerns.…”
Section: Letter To Editormentioning
confidence: 99%
See 1 more Smart Citation
“…SLEs are characterized by recurrent attacks followed by symptomatic remission, eventually resulting in the progressive accumulation of neurological deficits in MELAS 4 . Evidence from neuroimaging, such as the alterations of cerebral diffusion, perfusion, and metabolism, 5–7 has revealed the different characteristics between the acute SLEs stage and chronic stage in patients with MELAS. However, the neuropathological mechanisms of MELAS remain largely unknown and need to be further explored.…”
mentioning
confidence: 99%